Evaluating Claims to Avoid Pseudoscientific and Unproven Practices in Special Education. (March 2017) - Travers, Jason C.
Special education professionals are charged with using evidence-based practices, but various unproven, disproven, and pseudoscientific interventions continue to proliferate. Unproven and ineffective interventions emerge and are adopted for various reasons. Ineffective interventions are inevitably harmful and require professionals to adopt a conservative approach that both minimizes potential for harm and maximizes potential for educational benefit. This is fundamental to the evidence-based movement, but special education professionals may not recognize and avoid ineffective interventions. This article aims to improve recognition of potentially ineffective interventions by shedding light on aspects of science, pseudoscience, and some mistakes frequently made in evaluating claims of intervention effectiveness. By becoming familiar with the distinctions between science and pseudoscience, and by developing an understanding of how errors in thinking are used to promote and defend interventions unsupported by empirical evidence, special education professionals can better protect their students with disabilities from potential harms associated with ineffective practices.